Biofilm compressibility in ultrafiltration: A relation between biofilm morphology, mechanics and hydraulic resistance. (15th June 2019) - Jafari, Morez; Derlon, Nicolas; Desmond, Peter; van Loosdrecht, Mark C.M.; Morgenroth, Eberhard; Picioreanu, Cristian
Abstract: Poroelastic fluid-structure interaction models were coupled to experimental data to determine the effects of biofilm spatial distribution of mechanical and hydraulic properties on the biofilm hydraulic resistance and compressibility in membrane filtration processes. Biofilms were cultivated on ultrafiltration membranes for 20 and 30 days under high (0.28 bar) and low (0.06 bar) transmembrane pressure (TMP), in dead-end filtration mode. Subsequently, biofilms were subjected to a compression/relaxation cycles by step-wise TMP changes. Structural deformation of biofilms during compression was observed in-situ using optical coherence tomography. Experimental results show that the observed increase in the biofilm hydraulic resistance during compression is not necessarily accompanied by a detectable biofilm thickness reduction. A dual-layer biofilm model with a dense base and porous top layer could explain these observed results. Because porosity controls indirectly the mechanical response of biofilms under compression, results could be described without assuming a gradient in mechanical properties within the biofilm. The biofilm surface roughness did not significantly influence the water flux in this study. However, the fraction of biofilm base layer directly exposed to bulk liquid could be a good indicator in the determination of water flux. The main implications of this study for the design and operation of low-pressure membrane systems (e.g., MF and UF with fouling layer being the main filtration resistance) lays in the selection of favorable operational TMP and biofilm morphology. Highlights: OCT images linked to poroelastic models explain biofilm deformation and water flux. Increased hydraulic resistance was not accompanied by biofilm thickness reduction. Biofilm porosity controls indirectly the biofilm mechanical response to compression. Permeate flux through biofilm is dictated by a thin and dense base layer. A novel flux indicator based on biofilm morphology was proposed.